Effects of drop height on drop jump performance - Addie, C. D.; Arnett, J. E.; Neltner, T. J.; Straughn, M. K.; Greska, E. K.; Cosio-Lima, L.; Brown, L. E. (International Journal of Kinesiology & Sports Science, 2019)
Background: Drop jumps (DJ) are commonly implemented in plyometric training programs in an attempt to enhance jump performance. However, it is unknown how different drop heights (DH) affect reactive strength index (RSI), jump height (JH) and ground contact time (GCT). Objectives: The purpose of this study was to assess the effect of various DHs on RSI, JH, and GCT. Methods: Twenty volunteers with a history of plyometric training (Males = 13, Females = 7; age: 22.80 ± 2.69 yr, height: 175.65 ± 11.81 cm, mass: 78.32 ± 13.50 kg) performed DJs from 30 cm (DJ30), 45 cm (DJ45), 60 cm (DJ60), 76 cm (DJ76), and 91 cm (DJ91) and a countermovement jump (0 cm). A 16-camera Vicon system was used to track reflective markers to calculate JH; a Kistler force plate was used to record GCT. RSI was calculated by dividing JH by GCT. RSI and GCT were compared using a 2x5 (sex x DH) mixed factor repeated measures ANOVA, while JH was compared using a 2x6 (sex x DH) repeated measures ANOVA. Results: There were no interactions, but there was a main effect for sex for both JH (M>F) and GCT (F>M). JH demonstrated no main effect for DH: DJ30 (0.49 ± 0.11 m), DJ45 (0.50 ± 0.11 m), DJ60 (0.49 ± 0.12 m), DJ76 (0.50 ± 0.11 m), and DJ91 (0.48 ± 0.12 m). However, GCT showed a main effect where DJ30 (0.36 ± 0.10 s), DJ45 (0.36 ± 0.12 s), and DJ60 (0.37 ± 0.10 s) were not significantly different but were less than DJ76 (0.40 ± 0.12 s) and DJ91 (0.42 ± 0.12 s). Conclusions: Increasing DH beyond 60 cm increased GCT but did not affect JH, resulting in decreased RSI. Therefore, practitioners designing plyometric training programs that implement DJs may utilize DHs up to 60 cm, thereby minimizing GCT without compromising JH.